Critical approaches in the catalytic transformation of sugar isomerization and epimerization after Fischer－History, challenges, and prospects - Gao, Da-Ming; Zhang, Xun; Liu, Haichao; Fujino, Hidemi; Lei, Tingzhou; Sun, Fuan; Zhu, Jie; Huhe, Taoli (Green energy & environment, 2024)
The transformation of aldose to ketose or common sugars into rare saccharides, including rare ketoses and aldoses, is of great value and interest to the food industry and for saccharidic biomass utilization, medicine, and the synthesis of drugs. Nowadays, high-fructose corn syrup (HFCS) is industrially produced in more than 10 million tons annually using immobilized glucose isomerase. Some low-calorie saccharides such as tagatose and psicose, which are becoming popular sweeteners, have also been produced on a pilot scale in order to replace sucrose and HFCS. However, current catalysts and catalytic processes are still difficult to utilize in biomass conversion and also have strong substrate dependence in producing high-value, rare sugars. Considering the specific reaction properties of saccharides and catalysts, since the pioneering discovery by Fischer, various catalysts and catalytic systems have been discovered or developed in attempts to extend the reaction pathways, improve the reaction efficiency, and to potentially produce commercial products. In this review, we trace the history of sugar isomerization/epimerization reactions and summarize the important breakthroughs for each reaction as well as the difficulties that remain unresolved to date. [Display omitted] •Ketonization of reducing sugars are strongly dependent on the property of catalysts, solvents and heating method.•Sn-beta zeolite showed promising practical using in ketonization of several sugars.•Subcritical aqueous alcohol treatment is also a convenient method to produce rare ketoses.•It is still urgent to develop water tolerant and substrate-independent solid catalyst.